The Relevance of Maqamat wa Ahwal in Sufism for Gen Z: Theory, Urgency, and Spiritual Conception in the Digital Era - Renaningtyas, Della (Journal of Islamic and Social Studies, 2025)
This article discusses the relevance of the concepts of Maqamat and Ahwal in Sufism for Generation Z. Maqamat are stages in the spiritual journey towards Allah, while Ahwal are the inner experiences experienced during the journey. This concept provides a stable and meaningful direction for Generation Z in dealing with the complexities of modern life. Through a literature and qualitative approach, this article discusses the contribution of Generation Z in responding to identity politics at the local level and the importance of the Maqamat and Ahwal concepts in the development of a personal relationship with Allah and self-transformation towards moral and spiritual perfection.